2018
DOI: 10.1111/jop.12768
|View full text |Cite
|
Sign up to set email alerts
|

Growth‐regulated oncogene‐α from oral submucous fibrosis fibroblasts promotes malignant transformation of oral precancerous cells

Abstract: GRO-α from OSF-associated fibroblasts paracrinally promotes oral malignant transformation and significantly contributes to OSCC development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…It was found that oral sub-mucous fibrosis related fibroblasts expressed higher level of CXCL1 than normal fibroblasts and CXCL1 might function as a pre-cancerous promoter. 26 On the contrary, in patients diagnosed of gastric cancer with precancerous lesions, level of serum CXCL1 was significantly reduced while other inflammatory cytokines like IL-1, IL-6 were increased compared with control group, indicating the systematic activation of the immune system and an unusual activation pathway of CXCL1. 27 Though here we found precancerous lesions on tongue had statistical significance in prediction of lymphatic metastasis and OS, its clinical significance whether it could be a predictor in prognosis of OTSCC should need further exploration.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It was found that oral sub-mucous fibrosis related fibroblasts expressed higher level of CXCL1 than normal fibroblasts and CXCL1 might function as a pre-cancerous promoter. 26 On the contrary, in patients diagnosed of gastric cancer with precancerous lesions, level of serum CXCL1 was significantly reduced while other inflammatory cytokines like IL-1, IL-6 were increased compared with control group, indicating the systematic activation of the immune system and an unusual activation pathway of CXCL1. 27 Though here we found precancerous lesions on tongue had statistical significance in prediction of lymphatic metastasis and OS, its clinical significance whether it could be a predictor in prognosis of OTSCC should need further exploration.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, patients already diagnosed with OTSCC yet accompanied by another precancerous lesion on tongue were found to be related with higher risk of lymphatic metastasis and poorer prognosis than those who had no precancerous lesion on tongue. It was found that oral sub‐mucous fibrosis related fibroblasts expressed higher level of CXCL1 than normal fibroblasts and CXCL1 might function as a pre‐cancerous promoter 26 . On the contrary, in patients diagnosed of gastric cancer with precancerous lesions, level of serum CXCL1 was significantly reduced while other inflammatory cytokines like IL‐1, IL‐6 were increased compared with control group, indicating the systematic activation of the immune system and an unusual activation pathway of CXCL1 27 .…”
Section: Discussionmentioning
confidence: 97%
“…36 ROS may lead to doublestrand DNA breaks (DS-breaks) of epithelial cells leading to their malignant transformation. 36 The GRO-α secretion by OSF myofibroblasts via EGFR/ERK signaling, F-actin rearrangement, and stemness, 37 malignant transformation of the dysplastic oral keratinocytes through its CXCR-2 receptor. A recent paper published by Kim et al 38 has shown that CXCL-1, secreted by oral cancer cells in a paracrine manner promotes senescence in fibroblasts, and further propagates its senescent state via secretion of CXCL-1, and thereby establishes an autocrine loop (Figure 2, orange box).…”
Section: Molecular Orchestrators Of Senescence Associated Secretory Phenotypementioning
confidence: 99%
“…116 These MSCs can serve as a source of multipotent cells that can rapidly repopulate the wound in response to epithelial injury. 116 Ye et al 117 showed that growth-regulated oncogene-α (GRO-α) secretion by OSF fibroblasts promotes oral keratinocyte malignant transformation by augmenting EGFR/ERK signalling, F-actin rearrangement and stemness. Transformed keratinocytes can then acquire further genetic alterations with the evolution of more invasive clones.…”
Section: Rise Of Cancer Stem Cells-dichotomy Of Areca Nut Ingredientsmentioning
confidence: 99%